Lithological and structural anatomy of an unusually well exposed strike-slip fault pressure ridge in the Nanjieshan, western China. (December 2022) - Yang, Haibo; Huang, Xiongnan; Cunningham, Dickson; Zhang, Haoran; Yang, Xiaoping; Hu, Zongkai
Abstract: We combine field observations, drone photogrammetry, and petrographic and XRD analysis to document the internal lithological and structural variability of an exceptionally well-exposed strike-slip fault pressure ridge, in the northern Tibetan foreland. The ridge exposes alternating dm-m thick discolored zones of fault gouge, breccia, and cataclasite likely reflecting the original Riedel shear array and progressive widening of the fault zone as comminution, fluid pressures, mineral alteration, and strain hardening and weakening processes evolved and migrated vertically and laterally within the core. The principal fabric defines an internal foliation fan, and sinistral, oblique-thrust faults bound the ridge supporting a transpressive squeeze-up origin. Outcrop- and micro-scale grain size reduction, gouge formation, and calcite precipitation suggest that thermal pressurization, mechanical lubrication, fault-valve fluid cycling, and periodic gouge zone lock-up may have been important factors controlling fault slip behavior and seismic energy release. Local variations in the distribution and thicknesses of brittle fault rocks, strain intensity, alteration mineralogy and fault core fabrics are a sobering reminder that a single 2-dimensional exposure across any regional fault system will fail to capture the complex petrological, mineralogical, mechanical and rheological heterogeneity that is typical of an evolving intraplate strike-slip fault system, especially where it reactivates an older fault/shear zone. Highlights: Detailed structural and lithological variations of a pressure ridge are documented. Alternating zones of gouge, breccia and cataclasite are common and complexly arranged. The ridge is a sinistral transpressive squeeze-up with an internal foliation fan. Mineralogical and structural variations in core suggest complex slip behavior evolution. A single cross-fault exposure will not capture geometrical and mechanical complexity.